An Analyzing Locomotor Skill Profiles of Elementary Students - Agus Zafitra, Zikrillah; Andli Marta, Ibnu; Bakhtiar, Syahrial; Gusti Handayani, Sri (Universitas PGRI Palembang, 2025)
This investigation was undertaken to rigorously analyze the locomotor skill proficiency of students attending SD Negeri 03 Lima Kaum, Tanah Datar. Adopting a quantitative descriptive research design, the study sought to delineate, elucidate, and synthesize the spectrum of conditions and phenomena pertinent to the locomotor abilities exhibited by the student population under investigation. Data acquisition was facilitated through the administration of the locomotor subtest of the Test of Gross Motor Development-Second Edition (TGMD-2), a standardized and validated instrument for assessing fundamental movement skills. A purposive sampling strategy was employed to select a representative cohort of twenty students for participation in the study, ensuring focused data collection relevant to the research objectives. The resultant quantitative data were subsequently subjected to descriptive statistical analysis, specifically percentage distribution, to ascertain the prevalence of varying locomotor skill levels within the sampled population. The findings of this analysis revealed a heterogeneous distribution of locomotor skill classifications among the participants: (1) eight students (40%) demonstrated “Competent” locomotor skills, achieving scores within the 34-37 range; (2) five students (25%) were classified as exhibiting “Moderate” locomotor skills; (3) six students (30%) presented with “Deficient” locomotor skills; and (4) a single student (5%) was categorized as possessing “Inadequate” locomotor skills. The calculated mean locomotor skill level for the entire student sample fell within the “Moderate” classification. This central tendency suggests a potential area for pedagogical focus, indicating the possible necessity for the implementation of targeted interventions designed to enhance the fundamental locomotor competencies of this student population. Further research exploring the underlying factors contributing to these observed skill levels is warranted to inform the development of effective instructional strategies.